In-vitro anti-Helicobacter pylori activity and preliminary mechanism of action of Canarium album Raeusch. fruit extracts. (30th January 2022) - Yan, Jiahui; Peng, Chang; Chen, Pengting; Zhang, Weijia; Jiang, Cheng; Sang, Shuyi; Zhu, Weixing; Yuan, Yuemei; Hong, Yanjun; Yao, Meicun
Abstract: Ethnopharmacological relevance: Canarium album Raeusch. belongs to the Burseraceae family. Its ripe fruits, known as Qing Guo (QG) in Traditional Chinese Medicine (TCM), are used to treat sore throat, cough, and fish or crab poisoning. QG was reported to have antibacterial activity, and it exerted excellent anti- Helicobacter pylori ( H. pylori ) activity in our screening of abundant TCM. However, few studies have reported its anti- H. pylori activity and mechanism. Aim of study: The commonly used eradication therapies for H. pylori infection are antibiotic-based therapies. With the increasing antibiotic resistance of H. pylori, interest in finding alternative therapies has been aroused. This study investigated the phytochemistry profile, in vitro anti- H. pylori activity and possible anti-bacterial mechanism of QG extracts. Materials and methods: QG extracts were obtained by heat reflux extraction, ultrasonic extraction or liquid-liquid extraction with different solvents. The quantitative and qualitative phytochemical analyses were performed by colorimetric determination, high-performance liquid chromatography (HPLC), and UPLC-electrospray ionization mass spectrometry (ESI-MS). In vitro anti- H. pylori activity was assessed by broth micro-dilution method. Mechanism of action studies included morphological observation using electron microscopy, urease inhibition assay and determination of expression of virulence genes by RT-qPCR. Results: All QG extracts especially ethyl acetate extract (QGEAE) were rich in phenolic components, with the minimum inhibitory concentrations (MICs) on H. pylori of 39–625 μg/ml and minimum bactericidal concentrations (MBCs) of 78–1250 μg/ml. Both aqueous extract (QGAE) and QGEAE could induce the morphological and structural changes of H. pylori, inhibit urease activity with IC50 of 1093 μg/ml and 332.90 μg/ml, respectively, and down-regulate the virulence genes, such as vacA and cagA . Conclusions: QG may exhibit in vitro anti- H. pylori activity by inhibiting growth, destroying the bacterial structure and down-regulating the expression of virulence factors. Moreover, QG is the homology of food and TCM, which can be considered as a safe and convenient agent against H. pylori infection. Graphical abstract: Image 1 Highlights: Phytochemical constituents of Canarium album Raeusch. fruits (QG) were analyzed. QG showed anti- Helicobacter pylori ( H. pylori ) activity towards sensitive and antibiotic resistant strains. QG exhibited anti- H. pylori activity by inhibiting growth, destroying membrane and down-regulating virulence genes. QG could be served as a safe and convenient agent for H. pylori infection.